Analisis Pemikiran KH. Fahmi Basya tentang Matematika Islam - Ferayanti; Rahimah Embong; Hanif Md Lateh @Juned (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
The integration of mathematical concepts with Islamic values is very important to be applied as one way of character formation of the nation. KH Fahmi Basya began his research on the Qur'an since 1972 and summarized his research findings under the sub-field of Islamic mathematics in 1982. Through his discovery, the field of Islamic mathematics was one of the subjects of Universitas Islam Negeri Syarif Hidayatullah Jakarta in 2002 until this day. This study is a qualitative study that applies the content analysis design. Survey data through primary source of result of authorship of KH. Fahmi Basya, the book ‘Matematikaa Islam 1, Matematikaa Islam 2 dan Matematikaa Islam 3'. In addition, the data was also obtained by interviewing three key informants namely KH. Fahmi Basya, her manager and one field expert. The data was analyzed using a document analysis approach to the study material either primary or secondary. The results showed KH. Fahmi Basya’s thought in the field of Islamic mathematics among others with the creation of works in the form of scientific writing. His writings were full of ideas and thoughts among them in answering the phenomenon of numbers in Islam. In addition, in the form of humanitarian issues in the form of increased faith and confidence by learning Islamic mathematics. KH Fahmi Basya has a strong educational background in the field of mathematics, and added his love to the Qur'an. For that reason he is very concerned and creative to conduct research on the miracles of al-Qur'an through a mathematical approach. It could be concluded that Islamic Mathematics according to KH. Fahmi Basya’s thoughts are based on al-Qur’an and alSunnah DOI: https://doi.org/10.5281/zenodo.3236448